Sex Hormones as Potential Modulators of Vascular Function in Hypertension - Khalil, Raouf A. (Hypertension (Dallas, Tex. 1979), 2005)
The greater incidence of hypertension in men and postmenopausal women compared with premenopausal women has suggested gender differences in vascular function. Vascular effects of the female sex hormones estrogen and progesterone and the male hormone testosterone have been described. Sex steroid receptors have been identified in vascular endothelium and smooth muscle. Interaction of sex hormones with cytosolic/nuclear receptors initiates long-term genomic effects that stimulate endothelial cell growth but inhibit smooth muscle proliferation. Activation of sex hormone receptors on the plasma membrane triggers nongenomic effects that stimulate endothelium-dependent vascular relaxation via NO–cGMP, prostacyclin–cAMP, and hyperpolarization pathways. Sex hormones also cause endothelium-independent inhibition of vascular smooth muscle contraction, [Ca]i, and protein kinase C. These vasorelaxant/vasodilator effects suggested vascular benefits of hormone replacement therapy (HRT) during natural and surgically induced deficiencies of gonadal hormones. Although some clinical trials showed minimal benefits of HRT in postmenopausal hypertension, the lack of effect should not be generalized because it could be related to the type/dose of sex hormone, subjects’ age, and other cardiovascular conditions. The prospect of HRT relies on continued investigation of the molecular mechanisms underlying the vascular effects of sex hormones and identification of compounds that specifically target the vascular sex hormone receptors. Naturally occurring hormones and phytoestrogens may be more beneficial HRT than synthesized compounds. Also, the type/dose, time of initiation, and duration of HRT should be customized depending on the subject’s age and preexisting cardiovascular condition, and thereby enhance the outlook of sex hormones as potential modulators of vascular function in hypertension.